The Ḥanbalī school of law and Ibn Taymiyyah : conflict or conciliation - Al-Matroudi, Abdul Hakim I. (Culture and civilisation in the Middle East., 2006)
In this book, the life of the 14th century jurist Ibn Taymiyyah and his position within Hanbali tradition is analysed. It is an original piece of research, taking into consideration the issues involved in madhhab affilation and Hanbali fiqh.